Applications of machine learning in tumor-associated macrophages - Li, Zhen; Yu, Qijun; Zhu, Qingyuan; Yang, Xiaojing; Li, Zhaobin; Fu, Jie (Frontiers in Immunology, 2022)
Evaluation of tumor-host interaction and intratumoral heterogeneity in the tumor microenvironment (TME) is gaining increasing attention in modern cancer therapies because it can reveal unique information about the tumor status. As tumor-associated macrophages (TAMs) are the major immune cells infiltrating in TME, a better understanding of TAMs could help us further elucidate the cellular and molecular mechanisms responsible for cancer development. However, the complicated, high-dimensional, and heterogeneous data limited the extensive integrative analysis of cancer research. Machine learning algorithms are particularly suitable for oncology data analysis due to their flexibility and scalability to analyze diverse data types and strong computation power to learn underlying patterns from massive and complex data sets. With the application of machine learning in analyzing TME, and especially TAM’s traceable status, we could better understand the role of TAMs in tumor biology. Furthermore, we envision that the promotion of machine learning in this field could revolutionize tumor diagnosis, treatment stratification, and survival predictions in cancer research. In this article, we described key terms and concepts for understanding machine learning, reviewed the application of common methods in TAMs, and highlighted the challenges and future direction for TAMs in machine learning.